The benefit of late readings in patch testing depends both on allergen and patient characteristics. Issue 5 (31st October 2021) - Forkel, Susann; Schubert, Steffen; Dickel, Heinrich; Gina, Michal; Schröder‐Kraft, Claudia; Vieluf, Dieter; Brans, Richard; Kreft, Burkhard; Wurpts, Gerda; Geier, Johannes; Buhl, Timo
Abstract: Background: Patch test (PT) readings are recommended after 48 h and 72 h (D3). An additional day 7 (D7) reading has been suggested by some, although data on efficient patient selection are scarce. We investigated positive D7 reactions regarding (i) allergens in the baseline series and additional PT series of the German Contact Dermatitis Research Group (DKG) and (ii) characteristics of the patients tested. Methods: Retrospective, multicentre analysis of 190 allergens derived from 17 DKG test series in 4687 patients with an additional D7 reading. Patients were patch tested with the baseline series and additional series, if required. Occurrence of novel D7 reactions as well as increasing skin reactions from D3 to D7 was analysed separately. Results: Depending on the allergen tested, waiving D7 readings would have missed 4.4–26.8% of positive PT results. Patch test series with the highest number of novel D7 reactions were baseline series, metal series, and leather/shoe series. New positive reactions on D7 were associated with age over 50 years and with a negative irritant control containing sodium lauryl sulphate. Of note, application of the PT allergens for 48 h instead of 24 h was positively associated with late PT reactions. Conclusion: Within the most frequently tested allergens, without late readings, on average 11.7% of sensitizations would have been missed. Novel late reacting allergens were identified. This study comprehensively dissects patient‐, allergen‐ and test‐dependent parameters in support for D7 readings. We propose to always consider late readings individually based on effort‐benefit considerations. Abstract : Novel day 7 reactions are most likely in patients over 50 years of age, in patients with negative irritant controls on day 3, or if the patch test application time was 48 h instead of 24 h. Some test series are higher associated with novel day 7 reactions. Inconclusive patch test results on day 3 should trigger an additional reading on day 7. Abbreviation: SLS, sodium lauryl sulfate.